4D microstructural evolution in a heavily deformed ferritic alloy: A new perspective in recrystallisation studies. (June 2022) - Yildirim, C.; Mavrikakis, N.; Cook, P.K.; Rodriguez-Lamas, R.; Kutsal, M.; Poulsen, H.F.; Detlefs, C.
Graphical abstract: Abstract: We present a multiscale study on the recovery and recrystallisation of a heavily deformed (85% reduction in size) Fe–Si–Sn alloy using a combination of dark field X-ray microscopy (DFXM), synchrotron X-ray diffraction (SXRD) and electron backscatter diffraction (EBSD). By utilizing DFXM, we focus on a grain within the high stored energy (HSE) regions, and track it through consecutive isothermal annealing steps. The intra-granular structure of the as-deformed grain reveals deformation bands separated by ≈ 3 –5 ∘ misorientation. During the early stages of annealing, cells with 2–5 ∘ misorientation form while new nuclei appear. The recrystallized grains nucleate near prior grain boundaries, having a typical internal angular spread of < 0 . 05 ∘ . The SXRD results suggest no significant macroscopic texture change after annealing for 1400s at 610 ∘ C in the HSE regions. All results indicate that higher misorientation zones such as grain boundaries or junction points of deformation bands are preferential nucleation regions.